HOW BIG DATA ANALYTICS IMPROVES CUSTOMER RELATIONSHIP MANAGEMENT (CRM) - Mushtariy Shaimova Karim qizi (Modern American Journals, 2025)
The digital revolution has unleashed a tidal wave of data, with every online interaction—whether an email sent, a product purchased, or a social post shared—contributing to an ever-expanding landscape of information. In this environment, customer relationship management (CRM) stands at a pivotal crossroads: traditional approaches to customer engagement and retention are no longer sufficient to meet the rising expectations of today’s hyper-connected consumers. Enter big data analytics—a transformative force that enables organizations to harness the power of massive, complex datasets and turn them into actionable insights that drive business success.
Keywords: environment, customer relationship management (CRM); data analytics